Pengaruh Motivasi Kerja, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Badan Kepegawaian Daerah Kabupaten Labuhanbatu - Harahap, Kartini; Elvina, Elvina; Zelibu, Yanto (Journal of Innovative and Creativity, 2026)
This study aims to analyze the effect of work motivation, work discipline, and work environment on employee performance at the Regional Personnel Agency of Labuhanbatu Regency. This research uses a quantitative associative approach with a sample of 41 employees using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that partially, work motivation does not have a significant effect on employee performance, while work discipline and work environment have a positive and significant effect. Simultaneously, all variables significantly affect employee performance with a coefficient of determination (R²) of 0.496. The most dominant variable influencing employee performance is work discipline